Against the grain - Lovesey, Peter (Lovesey, Peter. Peter Diamond mystery, 2024)
"Detective Peter Diamond goes undercover at a seasonal festival in this delightful and bittersweet conclusion to the multi-award-winning series. Detective Peter Diamond, chief of the Avon and Somerset Murder Squad, is taking a short holiday in the country. His former colleague Julie Hargreaves has invited Diamond and his partner, Paloma, to visit the idyllic village of Baskerville (no relation to the Sherlock Holmes story, so he's told). It turns out Julie's invitation was not without ulterior motives. The woman who owns the village's largest dairy farm has been convicted of manslaughter following a terrible accident in her grain silo. Julie's ex-investigator instinct tells her there has been a miscarriage of justice and a murderer is on the loose-but Julie's been keeping secrets of her own, and can't take her inquiry any further. Diamond takes the bait; the case is a fascinating one, and he's quite enjoying his incognito information-gathering, getting to know the villagers as they prepare for their annual Harvest Festival. The deeper into the cow dung Diamond mucks, the more convinced he becomes there was foul play. But maintaining his innocent tourist facade becomes harder as he closes in on his suspects. To protect his alias, he might have to learn how to operate a tractor or drive a herd of wayward cows. He might even be forced to attend a hoedown-not that he'd dance, not even to catch a killer. Or would he? The curmudgeonly detective has plenty to learn about himself as he tries on some new hats: undercover private investigator; village detective; country gentleman"--